Analisis Sektor Unggulan dalam Rangka Pembangunan Daerah di Kabupaten Sumba Timur - Levina Kalla Malo; Adrianus Kabubu Hudang (Journal of Management and Creative Business, 2026)
Regional development aims to optimize available resources to boost regional economic growth. One effort to optimize resources and address government budget constraints is to analyze leading sectors, which are expected to accelerate economic growth. This study aims to analyze leading sectors in the economic development of East Sumba Regency for the 2020–2024 period based on Gross Regional Domestic Product (GRDP) data at constant prices. The analytical methods used include the Location Quotient (LQ) to identify basic and non-basic sectors, Shift Share to measure the competitiveness of sectors, and the Klassen Typology to group sectors based on their growth and contribution to the regional economy. The analysis results indicate that sectors with comparative and competitive advantages are mining and quarrying, manufacturing, construction, wholesale and retail trade, car and motorcycle repair, information and communication, health services and social activities, government administration, defense and social security, education, and other services, allowing them to be prioritized in more effective and sustainable regional economic development planning and policies.